Plant Nematology 2013
DOI: 10.1079/9781780641515.0459
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of nematodes.

Abstract: This chapter presents the history and development of nematicides; their active substances, modes of action, formulation and application; fate of nematicides in the environment, including their degradation, legislation, and their effects on non-target organisms, groundwater and ozone depletion (focusing on methyl bromide). Issues on human safety are also discussed, including the health risks associated to exposure during nematicide application and residues in foodstuffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…Imicyafos, a new nematicide based on organophosphate, was released in Japan in 2010, nearly 20 years after the release of fosthiazate, which had been a well‐accepted nematicide in several countries because of its relatively high nematode control efficacy . Currently, the most widely used non‐fumigant nematicides are organophosphates or carbamates, such as ethoprophos, fenamiphos, fosthiazate and oxamyl …”
Section: Introductionmentioning
confidence: 99%
“…Imicyafos, a new nematicide based on organophosphate, was released in Japan in 2010, nearly 20 years after the release of fosthiazate, which had been a well‐accepted nematicide in several countries because of its relatively high nematode control efficacy . Currently, the most widely used non‐fumigant nematicides are organophosphates or carbamates, such as ethoprophos, fenamiphos, fosthiazate and oxamyl …”
Section: Introductionmentioning
confidence: 99%
“…Meloidogyne javanica (Treub, 1885) Chitwood, 1949, M. incognita (Kofoid and White, 1919) Chitwood, 1949, M. arenaria (Neal, 1889) Chitwood, 1949and M. hapla Chitwood, 1949 are the most common species of root-knot nematodes, being responsible for at least 90% of all the plant damages caused by nematodes (Castagnone-Sereno, 2002). It was also found that the rootknot nematodes are the most predominant group that are targeted by 48% of the global nematicides used for all crops (Haydock et al, 2006).…”
mentioning
confidence: 99%
“…However, the number of commercially available chemical nematicides has declined in recent years due to their inherent toxicity and potential to cause environmental damage. Since the late 1970s, bans and restrictions for a majority of nematicides have left an urgent need for new nematode management solutions (Hague & Gowen, 1987;Haydock et al, 2013).…”
mentioning
confidence: 99%